Shipping Information Pipeline: An Information Infrastructure to Improve International Containerized Shipping - Thomas Jensen (Copenhagen Business School (CBS), 2017)
This thesis applies theoretical perspectives from the Information Systems (IS) research field to propose how Information Technology (IT) can improve containerized shipping. This question is addressed by developing a set of design principles for an information infrastructure for sharing shipping information named the Shipping Information Pipeline (SIP). Review of the literature revealed that IS research prescribed a set of meta-design principles, including digitalization and digital collaboration by implementation of Inter-Organizational Systems based on Electronic Data Interchange (EDI) messages, while contemporary research proposes Information Infrastructures (II) as a new IT artifact to be researched. Correspondingly, this thesis applies the concept of and design theory for II to improve containerized shipping. Activity Theory has guided the analysis of containerized shipping, following avocados on their journey from the trees in Africa, to the retail shelves in Europe, revealing the plethora of organizations, activities and documents involved. The implication being that containerized shipping becomes inefficiently; costly, unreliably, and risky. These are posited as the major impediments to creating a more efficient shipping industry, and a number of critical issues are identified. These include that shipments depend on shipping information, that shipments often are delayed due to issues with documentation, that EDI messages account for only a minor part of the needed information, that multiple fragmented II are used throughout, and finally, that there is an unleashed potential for IT to support containerized shipping. Based on the above, the SIP was designed, prototyped and evaluated which, through Internetenabled collaboration on shipments, ameliorates the previously mentioned critical issues and major impediments. This is accomplished primarily through increased transparency into the containerized shipping process and through providing direct access to source information about the shipments. Based on the prototypes an accumulated set of design principles for the design of SIP are articulated. In the particular context of Internet-enabled II utilizing the World Wide Web, an extension of design theory is proposed through the formulation of an additional metadesign principle: share meta-information only and govern access to detailed information by the source. Finally, the practical implications of SIP are estimated, including how it facilitates more efficient containerized shipping and in turn sustainable international trade. The positive acknowledgements of SIP prototypes support how II designed in accordance with the developed set of design principles can be used to significantly improve containerized shipping.
hdl:10398/9519
Keywords: 650